A maldição do petróleo em análise: uma revisão sistemática - Schmidt, Eduardo Moreira (Universidade Federal do Amazonas, 2018)
The relationship between the oil industry and economic growth is a well-studied topic in economics and political science, given the importance of the oil sector to the health of an energy organization in every country. At first, oil should offer real benefits to the economies of these countries, from the valorization of the domestic currency to the creation of new jobs, generating exceptional economic and social growth. However, much evidence shows that the abundance of these resources in a developing country hardly leads to expected economic and social growth. The opposite of what is expected in relation to the wealth of this resource determines a weak performance in the economy with the shrinking of other sectors of the industry, opacity in government finances and distancing from democracy. This enigmatic economic-social phenomenon is called the "oil curse."